Transmodern an art history of contact, 1920-60 - Kravagna, Christian 1962- (Manchester University Press, 2022)
Transmodern examines the global dimension of modern art by tracing the crossroads of modernisms in Asia, Europe and the Americas. It explores path-breaking transcultural art practices from the 1920s to the 1960s in the framework of decolonial movements and transcultural thinking.
Impressum: "This book was originally published as "Transmoderne: Eine Kunstgeschichte des Kontakts" (Berlin: b_books, 2017)"
Keywords: Geschichte 1920-1970; Unabhängigkeitsbewegung; Antirassismus; Ästhetik; Harlem renaissance; Abstrakte Kunst; Entkolonialisierung; Interkulturalität; Kunst; Antikolonialismus; USA; Indien